Some Problems of Modern Administrative Legal Proceeding (Aspect of World Justice) - Valentina Petrovna Esenova (Управленческое консультирование)
The article is devoted to the analysis of problems of the theory and practice of administrative legal proceedings in the Russian Federation and to prospects of its development. In it N. G. Salishcheva and V.D. Sorokin’s concepts significantly influenced the content of legal regulation of administrative justice are analysed. Gaps of the legislation and some problems of judicial enforcement which magistrates face by hearing of cases about administrative offenses are revealed.